THE IMPLICATURE IN THE PLAY ZOOTOPIA - Nurul Fatmawati; Nazila Nahrotun Nahdia (Dinamika Bahasa dan Budaya, 2017)
This study aims to analyze the implicature which is contained in a movie script entitled Zootopia. The writer tries to reveal the implied meaning in conversation in the movie. Also, the writer tries to divide the conversation into 4 maxims of implicature. In conversational implicature, there are 4 maxims which have to be understood to analyze the implied meaning in conversation. So the listener will know the implied meaning and the purpose of the speaker conveys the utterance. Those maxims are quantity, quality, relevance and manner. Those 4 maxims are contained in this movie script. But  most of the conversation uses the maxim of relevance either break or follow the rule.Keywords : implicature, maxim, implied meaning, conversation